Palliative care and catastrophic costs in Malawi after a diagnosis of advanced cancer: a prospective cohort study. Issue 12 (December 2021) - Jane Bates, Maya; Gordon, Miriam R P; Gordon, Stephen B; Tomeny, Ewan M; Muula, Adamson S; Davies, Helena; Morris, Claire; Manthalu, Gerald; Namisango, Eve; Masamba, Leo; Henrion, Marc Y R; MacPherson, Peter; et al.
Summary: Background: Inclusive universal health coverage requires access to quality health care without financial barriers. Receipt of palliative care after advanced cancer diagnosis might reduce household poverty, but evidence from low-income and middle-income settings is sparse. Methods: In this prospective study, the primary objective was to investigate total household costs of cancer-related health care after a diagnosis of advanced cancer, with and without the receipt of palliative care. Households comprising patients and their unpaid family caregiver were recruited into a cohort study at Queen Elizabeth Central Hospital in Malawi, between Jan 16 and July 31, 2019. Costs of cancer-related health-care use (including palliative care) and health-related quality-of-life were recorded over 6 months. Regression analysis explored associations between receipt of palliative care and total household costs on health care as a proportion of household income. Catastrophic costs, defined as 20% or more of total household income, sale of assets and loans taken out (dissaving), and their association with palliative care were computed. Findings: We recruited 150 households. At 6 months, data from 89 (59%) of 150 households were available, comprising 89 patients (median age 50 years, 79% female) and 64 caregivers (median age 40 years, 73% female). Patients in 55 (37%) of the 150 households died and six (4%) were lost to follow-up. 19 (21%) of 89 households received palliative care. Catastrophic costs were experienced by nine (47%) of 19 households who received palliative care versus 48 (69%) of 70 households who did not (relative risk 0·69, 95% CI 0·42 to 1·14, p=0·109). Palliative care was associated with substantially reduced dissaving (median US$11, IQR 0 to 30 vs $34, 14 to 75; p=0·005). The mean difference in total household costs on cancer-related health care with receipt of palliative care was −36% (95% CI −94 to 594; p=0·707). Interpretation: Vulnerable households in low-income countries are subject to catastrophic health-related costs following a diagnosis of advanced cancer. Palliative care might result in reduced dissaving in these households. Further consideration of the economic benefits of palliative care is justified. Funding: Wellcome Trust; National Institute for Health Research; and EMMS International.